A study of the linear transport in single electron transistor (set) using simon 2.0 simulators - 345678 Mohd. Norfarhan Nor Alam; Ahmad Radzi Mat Isa, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2007